A novel c.916C>A EDA gene pathogenic variant in a boy with X‐linked hypohidrotic ectodermal dysplasia. (20th December 2020) - Mintoff, D.; Pace, N. P.; Mercieca, V.; Bauer, P.; Borg, I.
Abstract : Click here for the corresponding questions to this CME article.